Hōkai rangi : a critical discourse analysis of the Department of Corrections five year strategy : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University, Palmerston North, New Zealand - McNab, Ian James (Massey University, 2023)
Hōkai Rangi is a publicly available document that outlines the five-year strategy for the Department of Corrections Aotearoa New Zealand, 2019 to 2024. This thesis uses a Critical Discursive Analysis of the document to identify the power relations that are represented through discourse which will show how Hōkai Rangi is representative of transformative discursive change and how it may become a reifying statement of continued discursive practice. I look at the dominant discourses and knowledges that have shaped correctional practice throughout the history of Western imprisonment and management of human risk. This gives the theoretical, cultural, and historical context for analysis. A subsequent analysis focuses on the clear and obvious, as well as opaque reifying of discursive power relations that trap the Department in its current practices, as well as some of the challenges to discourse that the document proposes. Throughout this work I use the theses on penology and the society of captives, proposed by Arrigo and Milovanovic (2010) to inform potential sites of resistance and spaces for discursive change that could support transformative change for the way in which human risk is conceptualised and managed. I also look to areas of practice that have the potential to enable frontline workers to effect discursive change.
Keywords: 440202 Correctional theory, offender treatment and rehabilitation